REPRESENTASI CINTA PADA ALLAH DALAM SYAIR RABI’AH AL-ADAWIYAH DAN SYAIR HUSAIN MANSHUR AL-HALLAJ (Kajian Sastra Bandingan): (Kajian Sastra Bandingan) - Tati Nurhayati (Tafhim Al-'Ilmi, 2019)
This article aims to examine and describe the representation love for God in the poems both of Rabi'ah al-Adawiyah and al-Hallaj. This study is a comparative literature study, in order to find the relation between the two poems. The method used in this study is descriptive analysis method and comparative method. The results of this study show the meaning of Rabi'ah al-Adawiyah’s love poems and al-Hallaj's love poems. Then it was found that there was a relation between similarities or similarities in terms of the main meanings both of poems, there were also differences in terms of certain meanings and in terms of the style of presentation. Key word: Representation of Love in Allah, Rabi'ah al-Adawiyah’s poems, al-Hallaj's poems. Abstrak Artikel ini bertujuan untuk mengkaji dan memaparkan mengenai representasi cinta pada Allah dalam syair Rabi’ah al-Adawiyah dan syair al-Hallaj. Kajian ini merupakan kajian sastra banding, guna menemukan keterkaitan antara kedua syair tersebut. Metode yang digunakan dalam kajian ini adalah metode deskriptif analisis dan metode komparatif. Hasil dari penelitian ini menunjukkan makna dalam syair cinta Rabi’ah al-Adawiyah dan syair cinta al-Hallaj. Kemudian ditemukan adanya keterkaitan kemiripan atau persamaan dalam segi makna pokok kedua syair tersebut, juga terdapat perbedaan pada segi makna tertentu dan dari segi gaya penyajiannya. Kata Kunci:Representasi Cinta Pada Allah, Syair Rabi’ah al-Adawiyah,Syair al-Hallaj.